SONGKOK CELLENG - Abdul Ghofur (Institut Agama Islam Syarifuddin Lumajang, 2020)
Songkok Celleng is the mention of headgear for men in terms of the Maduresecommunity or often referred to as a cap and kopyah. The head covering or known asSongkok Celleng is a complementary part in dressing for the santri (student in IslamicBoarding School), traditional clothing in the community to clothing for bureaucratswho have an implicit significance in its use. In this scientific work, the writer uses asemiotic qualitative method according to Charles Sanders Pierce who specificallydescribes that the sign is able to represent something else. In addition, Pierce alsodefines the sign as something that can not be separated from the object of referenceand understanding of the subject of signs with trichotomy: representamen,interpretants and objects. From the research conducted, the conclusions that can beshown by the author are: (1) Songkok celleng (representamen) is a santri identitycontaining philosophical meaning of obedience or submission (interpretant) in theform of a head covering (object). (2) Songkok celleng is always present with the spiritof nationalism introduced by the First President of Indonesia (Sukarno) that SongkokCelleng is a national identity also strengthened by government regulations issuedduring the Soekarno administration.